2018
DOI: 10.3390/ijerph15102284
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Surveillance System on Foodborne Diseases in Brazil after 10-Years of Its Implementation: Completeness Evaluation

Abstract: This study aimed to evaluate the data quality of the Brazilian Epidemiological Surveillance System on Foodborne Diseases (VE-DTA) through the evaluation of the completeness of the record after 10-years of its implementation. The study evaluated the measurement of completeness by quantifying ignored, incomplete or blank responses of the data items filled. The evaluation used the percentage of completion of these items regarding the total number of notifications registered in the system. We organized the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…This can be justified by the greater population density of these regions, corresponding with the higher number of reports of FBD [14]. It is also important to mention that in the Southeast region, the VE-DTA system presents the highest level of completeness when compared to other Brazilian regions[12]. Also, we observed that most outbreak reports were for those that occurred in urban areas (83.1%) compared to rural and peripheral areas.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This can be justified by the greater population density of these regions, corresponding with the higher number of reports of FBD [14]. It is also important to mention that in the Southeast region, the VE-DTA system presents the highest level of completeness when compared to other Brazilian regions[12]. Also, we observed that most outbreak reports were for those that occurred in urban areas (83.1%) compared to rural and peripheral areas.…”
Section: Discussionmentioning
confidence: 78%
“…Regarding the average time taken for investigation of the outbreaks, there was a decreasing trend after 2008 and 2009. We can justify this trend since the VE-DTA system started in 2007 and the following two years were probably years of adaptation, [12]. Thus, we observed that there was an improvement in the mean time taken for investigation over the 11 years [5].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…According to the Brazilian National System of Epidemiological Surveillance of FBD, in the Brazilian Midwest region (location of the Federal District), 55% of the FBD outbreaks occurred from home food ingestion [11,25]. The high number of FBD notifications at home evidences the need to evaluate good food preparation practices in these places, to improve food-handling practices, and to reduce cases of FBDs in the domestic environment [18].…”
Section: Discussionmentioning
confidence: 99%
“…Consumers/food handlers do not see themselves or a family member as a contamination source or as susceptible to the risk of FBD [9]. These facts contribute to the absence of direction in educational campaigns and training for the public [4,10,11].…”
Section: Introductionmentioning
confidence: 99%